Antibiotic Treatment Response of Chronic Lung Diseases of Adult Sheep in the United Kingdom Based upon Ultrasonographic Findings. (26th May 2014) - Scott, Phil
Abstract : Examination of the lungs of adult sheep with chronic respiratory diseases was readily achieved using both 5 MHz linear and sector scanners. Superficial lung abscesses in eight sheep appeared as anechoic areas containing multiple hyperechoic dots bordered distally by a broad hyperechoic capsule. Unilateral fibrinous pleurisy (2 sheep) appeared as an anechoic area containing a hyperechoic latticework. Ovine pulmonary adenocarcinoma (OPA) lesions appeared as sharply demarcated hypoechoic areas in the lung parenchyma initially in the cranioventral lung lobes (21 sheep) with lesions also present in the caudodorsal diaphragmatic lobe (11 sheep); abscesses and areas of calcification within the OPA tumour mass were also identified. Daily treatment with procaine penicillin for 30 consecutive days was successful in both sheep with unilateral fibrinous pleurisy and six sheep identified with superficial lung abscesses measuring 2–8 cm in diameter; only one of two sheep with more extensive lesions recovered. Auscultation of the chest failed to detect adventitious sounds in any of the ten sheep with lung abscesses; normal breath sounds were reduced over the area of fibrinous pleurisy; no pleuritic rubs were heard. Wheezes and crackles auscultated in some OPA cases and did not correlate well with lesions detected ultrasonographically.